Histopathological Examination Findings in Ligature Mark in Post-Mortem Cases of Asphyxial Deaths: A Prospective Study - Khanna, Kunal; Jakhar, Jitender Kumar; Dagar, Tarun; Titiksha; Gill, Dr. Meenu; Pal, Vijay; Yadav, Gajender (International Journal of Innovative Research in Medical Science, 2024)
Background: Hanging and ligature strangulation are violent forms of asphyxia deaths. Forensic histopathology of these cases, a microscopic analysis of various changes at cellular or tissue level helps to find out the cause of death including solving a crime mystery. Aim & objectives: To differentiate between the cases of hanging and ligature strangulation by histo-pathological examination of skin and subcutaneous tissues of ligature mark. To differentiate between ante-mortem and post-mortem hanging by studying the histo-morphological features of ligature mark. Material & methods: Skin and subcutaneous tissues of ligature mark in 64 post-mortem cases brought for autopsy with alleged history of hanging and ligature strangulation are studied in a tertiary care centre of Haryana. 60 cases were of hanging while 04 were of ligature strangulation. Results: Out of 60 cases of hanging, compression was present in 59 (98%) cases, breaking in 58 (96%) cases, wrinkling in 55 (92%) cases, and all three were present in 53 (88%) cases. All three features were also present in 04 (100%) cases of strangulation. And out of 60 cases of hanging, congestion was present in 51 (85%) cases, infiltration in 38 (63%) cases, haemorrhage in 34 (57%) cases and all three were present in 25 (41%) cases. All three features were also present in 04 (100%) cases of strangulation. Conclusion: The present study emphasizes the implementation of histopathological examination of skin in all the cases of asphyxial death where compression of neck took place, as a routine procedure. It concludes that a detailed evaluation of the gross and histopathological findings of the neck structures, if undertaken as a routine would be more conclusive in establishing the cause and manner of death to aid the administration of justice.